2019
DOI: 10.1371/journal.pone.0223002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with the extract from Eucommia ulmoides leaves changed epithelial restitution and gut microbial community and composition of weanling piglets

Abstract: This study was conducted to compare the effects of Eucommia ulmoides leaves (EL) in different forms (EL extract, fermented EL, and EL powder) with antibiotics on growth performance, intestinal morphology, and the microbiota composition and diversity of weanling piglets. Compared to the control group, the antibiotics and EL extract significantly increased the average daily gain and decreased the feed: gain ratio as well as the diarrhea rate (P < 0.05). The EL extract significantly decreased the crypt depth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
(48 reference statements)
4
16
1
Order By: Relevance
“…In the present study, dietary ELE supplementation improved the activities of AKP and LAP in BBM, indicating that ELE played an important role in promoting larval intestinal development. Similar results were also observed in early-weaned piglets with incomplete digestive tract development (24,68) .…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, dietary ELE supplementation improved the activities of AKP and LAP in BBM, indicating that ELE played an important role in promoting larval intestinal development. Similar results were also observed in early-weaned piglets with incomplete digestive tract development (24,68) .…”
Section: Discussionsupporting
confidence: 85%
“…This might have been due to the strong aromatic compounds in E. ulmoides leaf, which might have affected the palatability of the feed. However, our results differ from some previous studies (10,11), which might have been due to different processing technologies and amounts of ELE supplements used, while ELE supplements had no negative effects on growth performance. Human consumption of meat products containing a large amount of fat may pose a threat to health; long-term consumption may induce cardiovascular diseases and obesity (20).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies into the potential of Eucommia ulmoides as a feed supplement in Chinese herbal medicine have been gradually developed. Previous studies focused on the effects of Eucommia ulmoides leaf and its extracts on growth performance and antioxidant activity in pigs (9)(10)(11). However, at present, there are few studies on the effect of Eucommia ulmoides leaf extracts (ELE) on lipid metabolism in growing-finishing pigs, and the optimal supplement level is also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional herb widely used in East Asia, Eucommia ulmoides (EU) has many functions in human including enhancing bones strength, antioxidant capacity, immunity and reducing body fattiness [3]. In recent years, EU has been reported as feed additive in rabbit [4], pig [5,6], chicken [7,8] and sh [9][10][11]. Studies have shown that EU promoted the esh quality by increasing muscle collagen of aquatic animals, such as eel Anguilla japonica [12], crucian carp Carassius auratus gibelio [13], grass carp Ctenopharyngodon idellus [9,14] and white shrimp Penaeus vannamei [15], but the mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%